Social criticism through humour in the digital age: multimodal extension in the works of Aleix Saló - Muñoz-Basols, J; Massaguer Comes, M (Berghahn Journals, 2018)
Numerous authors of comics and graphic novels have used the economic crisis in the Iberian Peninsula as a narrative frame for social criticism. Prominent among them is the Catalan cartoonist Aleix Saló, who burst upon the comics scene with his animated YouTube video ‘Españistán’ – a booktrailer of his graphic novel, Españistán. Este país se va a la mierda (2011) [Españistán. This Country is Going to Hell]. This article shows how Saló offers a humorous and didactic portrait of the devastating effects of the economic crisis: He does this first through multimodality (the use of specific shapes, selected colours, fonts, components of orality), and, second, by creating ‘multimodal extensions’, i.e., relations of intertextuality between published books and booktrailers. This analysis serves as a case study of the multimodal techniques that authors use to shape and develop their work in the context of the powerful relationship between text and image in the digital age.